A CONCEPTUAL OF STUDY ON RADICAL PERSUASIVE COMMUNICATION: A RISK FOR FUTURE GENERATIONS - Wardatul Hayat Adnan; Abdul Hamid Saifuddin; Ireena Nasiha Ibnu, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Radical organisations frequently target young adults, especially college students, to enlist them as cadres for their movements all over the world. They are recruited in a variety of ways, with the use of cyberspace being particularly prevalent. These extremists no longer use face-to-face interactions in the physical world to promote extremism in the age of the internet. Instead, they use the internet and information technology. These radical groups frequently take advantage of the widespread use of the internet, social media, and social networking tools to spread their beliefs, advance their doctrines, identify and recruit potential cadres, and even to call for jihad against the West. The present study aims to explore the reasons for radical organisations in targeting young adults in delivering their propaganda. Meta-Analysis was conducted through a narrative review of findings from multiple primary research studies on various studies to derive more robust conclusions and identify patterns and consistencies across different studies. Factors contributed are idealism and passion, vulnerability, active and energy, access to education and resources as well as due to long-term commitment. Radical organisations exploit this idealism to recruit young adults who may be more willing to engage in radical activities to achieve their goals and also to provide the manpower needed to carry out their agendas. Additionally, college students may have access to resources, such as meeting spaces, funding, and a network of like-minded individuals, which can further the goals of radical organisations and the ability to provide a constant stream of recruits and sustain the organisation's activities over time as most young adults prioritise their education, personal growth, and other non-radical activities. Thus, it is crucial to promote critical thinking, media literacy, digital literacy and open dialogue to empower young adults to make informed decisions and resist the influence of radical organisations.